Analisis Strategi Manajemen PT Hanjaya Mandala Sampoerna Tbk. Untuk Menjadi Market Leader dalam Industri Rokok - Sri Septia; Riris Loisa (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of research at PT HM Sampoerna, Tbk is to assess the company's business in the period 2013-2017. The results of the business assessment of each company can be information for investors and creditors to make a decision whether it is good for them to rotate the assets they have in the company. Business performance assessment conducted by the author at PT HM Sampoerna, Tbk is analyzing the SWOT, PORTER, PEST (Political, Economic, Social, and Technology) strategies, analyzing financial statements, and analyzing bankruptcy. The author uses a mixture of qualitative and quantitative methods in the research approach by using the income statement and balance sheet obtained from secondary data where all data is publicly available and can be accessed by anyone. Data analysis uses library research and analysis procedures. The results showed the level of leverage ratios and the level of liquidity ratios at PT HM Sampoerna, Tbk experienced fluctuations in each year but remained above the average industry company. While the level of profitability ratios has increased and is also well above the average industry company. The results of the analysis of the z score of PT HM Sampoerna, Tbk are far from the level of bankruptcy. Researchers can give advice to PT HM Sampoerna, Tbk to improve their income by changing credit sales to cash sales and also by looking at the strengths, weaknesses, opportunities and obstacles owned by PT HM Sampoerna, Tbk.